2011
DOI: 10.1016/j.bbamcr.2011.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to simvastatin-induced toxicity is partly determined by mitochondrial respiration and phosphorylation state of Akt

Abstract: Statins are widely used to prevent cardiovascular diseases. They are well-tolerated, with side-effects mainly seen in skeletal muscle. How these side-effects are caused is unknown. We compared isolated primary mouse skeletal muscle myocytes, C2C12 myotubes and liver HepG2 cells to detect differences that could uncover why statins are toxic in skeletal muscle but less so in the liver. 10μM simvastatin caused a decrease in mitochondrial respiration in the primary mouse myocytes and C2C12 myotubes, but had no eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
63
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 46 publications
10
63
1
Order By: Relevance
“…Our findings are difficult to reconcile with previous reports linking Akt to cardioprotection (30), but the differences may be related to the duration of statin administration. Dephosphorylation of Akt in statintreated C2C12 myotubes was previously described (35). Our studies further revealed the upregulation of autophagy through ULK1.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Our findings are difficult to reconcile with previous reports linking Akt to cardioprotection (30), but the differences may be related to the duration of statin administration. Dephosphorylation of Akt in statintreated C2C12 myotubes was previously described (35). Our studies further revealed the upregulation of autophagy through ULK1.…”
Section: Discussionsupporting
confidence: 58%
“…Statins have been reported to decrease superoxide production, in part through downregulation of nicotinamide adenine dinucleotide phosphate oxidase activity (8). Statins also are reported to improve mitochondrial function (26,51), although they have deleterious effects in skeletal muscle (19,27,35,36).…”
mentioning
confidence: 99%
“…Previous work from our group suggested that simvastatin-induced myotoxicity might be related to inhibition of the phosphorylation and thereby activation of AKT [14]. As shown in Fig.…”
Section: Introductionmentioning
confidence: 84%
“…Our data agree with previous experimental and human studies. Indeed, simvastatin causes a decrease in mitochondrial respiration in primary mouse myocytes and induces myotube atrophy and cell loss associated with impaired mitochondrial respiratory capacity, mitochondrial oxidative stress and apoptosis in primary human skeletal myotubes (24).…”
Section: Discussionmentioning
confidence: 99%